Anti‐envelope antibody responses in highly exposed seronegative individuals may be associated with protection from HCV infection. Issue 10 (17th June 2020) - Mina, Michael; Underwood, Alexander; Eltahla, Auda; Wu, Bing‐Ru; Walker, Melanie R.; Bull, Rowena A.; Lloyd, Andrew R.
Abstract: In rare cases, individuals with a history of long‐term injecting drug use remain seronegative and aviraemic, despite prolonged and likely repeated exposure to Hepatitis C virus (HCV) through high‐risk behaviour. We describe anti‐HCV Envelope (E) antibody responses in a prospective cohort of carefully defined highly exposed but uninfected subjects (HESN) and comparison subjects who were also high risk and uninfected, but rapidly became HCV infected (Incident). Longitudinally collected samples from HESN cases (n = 22) were compared to Incident controls (n = 22). IgG, IgM and IgA from sera were tested by ELISA to genotype 1a and 3a E glycoproteins, and recombinant genotype 1a E2 antigen. IgG subclass isotyping was performed for those positive for IgG. Virus‐neutralizing activity was assessed on HCV pseudoparticles, and HCV E–specific B cells analysed using flow cytometry. A significant minority of HESN cases (n = 10; 45%) had anti‐E, predominantly in the IgG2 subclass, which was not found in the pre‐infection time point of the Incident cases (n = 1; 5%). A subset of the HESN subjects also had neutralizing activity and HCV‐specific B cells detected significantly more than Incident cases pre‐infection. In conclusion, the HESN phenotype is associated with IgG2 anti‐E antibodies, neutralization activity and HCV E–specific memory B cells. These findings suggest that HESN subjects may be resistant to HCV infection through humoral immune‐mediated mechanisms.